CONSTITUTION WITHOUT A STATE: THE FORMATION OF THE KINGDOM OF SCS AND “THE VIDOVDAN” CONSTITUTION IN THE CONSTITUTIONAL LAW CURRICULUM IN YUGOSLAVIA’S SUCCESSOR STATES - MILOŠEVIĆ, Srđan (Pravni zapisi, 2021)
“The Vidovdan” Constitution of the Kingdom of Serbs, Croats, and Slovenes, rendered on 28 June 1921, one hundred years after its adoption, remains an unavoidable topic and an occasion for discussions about the reasons for the failure of the Yugoslav state. The unitarian-centralist system unanimously criticized today as an inadequate constitutional form for the functioning of a complex community such as Yugoslavia was once legitimized by the concept of national unity of Serbs, Croats, and Slovenes. The national conception, the type of state system, and the related disagreements are part of both the political and constitutional history of the states that emerged from the disintegration of Yugoslavia. This paper analyses the content of textbooks of Constitutional Law that are in use at law schools in the successor states, which have existed continuously since the breakup of Yugoslavia until today and are used to educate the vast majority of lawyers in these states. The way in which the shared constitutional history from the first decade of Yugoslavia is presented after the collapse of the socialist paradigm (that mainly was unison) largely follows the national borders of the successor states in terms of its content and interpretation.
Keywords: Kingdom of Serbs, Croats and Slovenes; The “Vidovdan” Constitution; Constitutional Law; Textbooks